Restricted repair of aflatoxin B1 induced damage in alpha DNA of monkey cells. - Leadon, S A (1983)
We have investigated the processing of adducts formed by covalent binding of aflatoxin B1 (AFB1) to DNA in confluent cultures of African green monkey cells. Repair synthesis elicited by AFB1 adducts was deficient in alpha DNA sequences compared to that in bulk DNA, although the initial levels of modification were the same for these DNAs. The removal of the primary initial adduct, AFB1-N7-Guanine, was deficient in alpha DNA and the kinetics of its loss resembled those previously reported for removal from total DNA in xeroderma pigmentosum cells of complementation group A. Spontaneous loss of the AFB1 moiety or the concomitant loss of the guanine to yield an apurinic site account for these results. The formation of the more chemically stable secondary product, AFB1-triamino-Pyrimidine, occurred more rapidly and to a greater extent in alpha DNA than in bulk DNA, probably because of slower removal of the primary product. The excision repair patch size for AFB1 adducts in alpha DNA was only 10 nucleotides compared to 20 nucleotides for repair of AFB1 adducts in bulk DNA. Irradiation of cells with low doses of UV prior to or immediately after treatment with AFB1 increased the rate and extent of removal of AFB1 adducts from alpha DNA to the levels found in the bulk DNA, indicating that the formation of pyrimidine dimers or their repair may alter the chromatin structure of alpha DNA sufficiently to facilitate its repair.